Dynamics of the triplet-pair state reveals the likely coexistence of coherent and incoherent singlet fission in crystalline hexacene - Monahan, Nicholas R.; Sun, Dezheng; Tamura, Hiroyuki; Williams, Kristopher W.; Xu, Bolei; Zhong, Yu; Kumar, Bharat; Nuckolls, Colin; Harutyunyan, Avetik R.; Chen, Gugang; Dai, Hai-Lung; Beljonne, David; et al. (Nature chemistry, 2017)
The absorption of a photon usually creates a singlet exciton (S 1 ) in molecular systems, but in some cases S 1 may split into two triplets (2×T 1 ) in a process called singlet fission. Singlet fission is believed to proceed through the correlated triplet-pair 1 (TT) state. Here, we probe the 1 (TT) state in crystalline hexacene using time-resolved photoemission and transient absorption spectroscopies. We find a distinctive 1 (TT) state, which decays to 2×T 1 with a time constant of 270 fs. However, the decay of S 1 and the formation of 1 (TT) occur on different timescales of 180 fs and <50 fs, respectively. Theoretical analysis suggests that, in addition to an incoherent S 1 → 1 (TT) rate process responsible for the 180 fs timescale, S 1 may couple coherently to a vibronically excited 1 (TT) on ultrafast timescales (<50 fs). The coexistence of coherent and incoherent singlet fission may also reconcile different experimental observations in other acenes. Singlet fission — the splitting of a singlet exciton into two triplets — is a process that could be exploited to improve the power conversion efficiency of solar cells. Spectroscopic data now suggest that coherent and incoherent mechanisms for singlet fission in crystalline hexacene coexist and occur on different timescales.